Considerations of the productive restructuring process in Brazil and its implications for workers and education (Práxis Educativa, 2009)
This article aims to discuss the profile that is required of workers in current forms of production. This is done by considering the productive restructuring process that took place in Brazil since the 1990’s. This process presents implications to different social organizations, especially to the State and the institutions related to it, for example the schools. The analysis of the primary and secondary sources related to the basic education reforms implemented in the same decade reveals the valuing of work competencies such as flexibility and the capacity to adapt. The article presents reflections on the rhetoric used to justify educational reforms, pointing out its underlying ideology and the actions performed by the Brazilian State, as well as the structural limits of the capitalist system for the social inclusion of the whole population. Keywords: Productive restructuring. Work and education. Basic education.